2021
DOI: 10.1097/pai.0000000000000942
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance and Prognostic Value of SOX2 Protein Expression in Patients With Oral Squamous Cell Carcinoma

Abstract: Objectives: Cancer stem cells are a small group of highly tumorigenic cells with the trend of self-renewal, tumor progression, metastasis, recurrence, and therapeutic resistance. SOX2 is an important cancer stem cell marker that is involved in tumorigenesis and correlated with aggressive features in various types of malignancies. The present study was aimed to investigate the expression of this biomarker in neoplastic tissues of oral squamous cell carcinoma (OSCC) to determine whether it has the potential to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…29,30 Furthermore, Ghazaghi and colleagues also observed a correlation between increased SOX2 expression and larger tumor sizes, more lymph node metastasis, and lower survival rates in oral squamous cell carcinoma patients. 31 Regarding SOX2, our study exhibited a low expression in cases with unpleasant outcomes, without correlation to neither survival rate nor clinicopathologic features. Solely an association of lower SOX2 expression with higher histopathologic grade was found in MEC patients.…”
Section: High Expression Low Expressionmentioning
confidence: 56%
See 1 more Smart Citation
“…29,30 Furthermore, Ghazaghi and colleagues also observed a correlation between increased SOX2 expression and larger tumor sizes, more lymph node metastasis, and lower survival rates in oral squamous cell carcinoma patients. 31 Regarding SOX2, our study exhibited a low expression in cases with unpleasant outcomes, without correlation to neither survival rate nor clinicopathologic features. Solely an association of lower SOX2 expression with higher histopathologic grade was found in MEC patients.…”
Section: High Expression Low Expressionmentioning
confidence: 56%
“…Most studies regarding the role of SOX2 in different types of cancers such as malignant colorectal tumors, breast cancer, and oral squamous cell carcinoma demonstrated that the increase in expression of SOX2 has a relationship with tumorigenesis and aggressive behavior of most of the malignant tumors, which can lead to the poor prognosis of the patients 29,30. Furthermore, Ghazaghi and colleagues also observed a correlation between increased SOX2 expression and larger tumor sizes, more lymph node metastasis, and lower survival rates in oral squamous cell carcinoma patients 31…”
Section: Discussionmentioning
confidence: 99%